2015 Soybean Production in Southeast Kansas - Gretchen Sassenrath; I. A. Ciampitti; D. E. Shoup; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2016)
Crop performance and yield varies as a function of the growing environment and soil properties within the field. Optimal soybean planting in southeast Kansas usually occurs from mid-May to mid-June for full-season or late-June to early-July for doublecropped soybean. Planting is timed to capture fall rains and cooler temperatures during critical periods of bean development and yield formation and avoid mid-summer heat and drought. Changing planting configuration (row spacing and plant population), timing of planting, and cultivar selection are methods of optimizing soybean production for different growing environments.
Keywords: soybean